Hodnocení finanční situace společnosti a návrhy na její zlepšení - Zachařová, Markéta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Cílem bakalářské práce je hodnocení finanční situace společnosti AVX Czech Republic, s.r.o. od roku 2013 po rok 2018 pomocí metod finanční analýzy. V první části práce jsou rozebrány ukazatele finanční analýzy z teoretického hlediska. Druhá část obsahuje informace o uvedené společnosti spolu s analýzou současného stavu pomocí uvedených ukazatelů. Ve třetí části jsou navržena opatření vedoucí ke zlepšení finanční situace společnosti.

The subject of this bachelor thesis is the evaluation of the financial situation of AVX Czech Republic, s.r.o. from 2013 to 2018 using financial analysis methods. The first part of the thesis deals with the definition of the indicators of financial analysis from a theoretical point of view. The second part contains information about this company along with the analysis of the current situation using the indicators. The third part proposes measures which aim to improve the financial situation of the company.
Evaluation of the Financial Situation in the Company and Proposals to its improvement
Keywords: finanční analýza; finanční situace společnosti; ukazatel; společnost; financial analysis; financial situations of the company; indicator; company